Mitigating Hospital-Onset Clostridioides difficile: Evaluation of a Standardized Environmental Hygiene Program in Eight Hospitals. (October 2020) - Carling, Philip; O'Hara, Lyndsay; Harris, Anthony; Olmsted, Russell
Abstract : Background: Despite ongoing efforts over the past 3 decades, hospital-onset Clostridioides difficile infection (HO-CDI) continues to challenge interventions aimed at its prevention and control. We describe the impact of a model environmental services (EVS) program on the incidence of HO-CDI across 8 hospitals that are part of a nationwide integrated health system. Methods: Eight acute-care hospitals with 44–532 beds (mean, 263 beds) in 6 states with stable endemic HO-CDI incidence densities independently implemented identical sporicidal environmental hygiene interventions in 2017. The program combined the use of a hydrogen peroxide/peroxyacetic acid surface disinfectant for all patient-zone hygienic cleaning combined with a structured model EVS cleaning program that included optimized cleaning and disinfection technique, staff training, and auditing with objective performance feedback, which aligned with 2008 HICPAC/CDC categories I and II as well as 2010 CDC Guidance Level II monitoring program recommendations. After a 3-month phase-in, we compared NHSN-reported LabID HO-CDI SIRs for 18 months before and 12 months after implementation of the program. Results were not shared between sites and data were not collated by the authors until a year after the postintervention results were initially available. Multiple possible confounding factors were evaluated and determined not to have identifiably affected the outcome. Results: Mean preintervention HO-CDI SIRs over the 18 months measured ranged from 0.5 to 1.4 (mean, 1.0 for the group). Following the wash-in period, SIRs decreased precipitously in all sites to a mean of 0.42 for the group by the end of 12 months of the intervention. ( P < .0001) (Fig. 1). Individual site improvement ranged from 20% to 92% (mean, 57%) (Fig. 2.) Conclusions: Overall, HO-CDI SIRs decreased almost 60% in the study hospitals following daily sporicidal disinfection cleaning of all patient-zone surfaces in association with ongoing programmatic optimization of cleaning practice. As predicted by earlier single-site studies reporting a favorable impact of sporicidal disinfectant cleaning in outbreak settings, this multisite quasi-experimental study has illustrated the substantial potential impact of hospital-wide sporicidal disinfection integrated with objectively sustained optimized thoroughness of cleaning to decrease the incidence of HO-CDI. Funding: None Disclosures: None